Condensed phase corrosion of P91 and DSS 2205 steels at advanced oxygen‐fired pressurized fluidized bed combustion plants. Issue 4 (25th October 2020) - Li, Kaiyang; Zeng, Yimin; Luo, Jing‐Li
Abstract: To achieve the targets of high energy efficiency and reduced CO2 emission, advanced oxygen‐fired pressurized fluidized bed combustion technology is being developed. The generated flue gas condensates are very corrosive, but very limited information is available to select appropriate alloys for the cost‐effective construction and long‐term safe operation of flue gas components. Thus, this study investigated the corrosion performance of P91 and DSS 2205 steels in the simulated condensates at 60°C–150°C. The dominant reactions on the two steels were considerable oxide formation and high chemical dissolution of the formed oxides instead of localized pitting. The increase in temperature leads to an exponential increase in the long‐term corrosion rates of the steels. Benefited from its high Cr and Mo contents, DSS 2205 steel exhibited much better corrosion resistance, and the formed surface scales consisted of inner Fe‐enriched and outer Cr‐enriched oxides in which Cr2 O3 was transformed into Cr(OH)3 with the increase in temperature. The corrosion products on P91 steel consisted of inner Cr–Fr–Mo oxides and outer Fe‐enriched oxides, which were porous and unable to protect the steel. Graphical abstract: This study investigated the corrosion performance of P91 and DSS 2205 steels in the simulated condensates of advanced oxygen‐fired pressurized fluidized bed combustion plants. The dominant reactions on the two steels were considerable oxide formation and high chemical dissolution of the formed oxides instead of localized pitting. Benefited from its high Cr and Mo contents, DSS 2205 steel exhibited much better corrosion resistance.